Treatment of aortic pseudoaneurysm with interventional procedure - HUANG, Lian-jun; YU, Fei-cheng; SUN, Li-zhong; TIAN, Liang-xin; CHU, Jun-min; LÜ, Jian-hua; JIN, Jing-lin; JIANG, Shi-liang (Chinese medical journal, 2006)
The prognosis of aortic pseudoaneurysm is bad because it usually threats to life by hemorrhea.Conventional surgical repair is usually associated with high morbidity and mortality, especially in patients with poor condition. Recent reports have shown promising results with endovascular treatment as a less invasive alternative to surgery. Fourteen patients with aortic pseudoaneurysms were treated by interventional procedure in our hospital.